Rare and fatal complications of tonsillectomy: sudden pneumothorax and extensive subcutaneous emphysema. Issue 7 (July 2022) - Liu, Yanquan; Yan, Zhimin; Guo, Huidong; Xu, Qinglin; Li, Zuotao; Lin, Jie
Tonsillectomy is a common, minimally invasive, and relatively safe surgical operation. Although the surgical technology for such minor operations is mature and widely available in most countries worldwide, postoperative adverse complications occur and may be hazardous and fatal. Our article presents the details of a 4-year-old boy who suddenly developed pneumothorax and systemic extensive subcutaneous emphysema after tonsillectomy. He received professional treatment from a multi-disciplinary team (MDT) and timely rescue in our hospital; however, he died tragically. To this end, there is an urgent need to raise clinicians' awareness of the potentially fatal and rare complications that can occur after tonsillectomy.